-3(x+6)=3-(-4)

Simple and best practice solution for -3(x+6)=3-(-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(x+6)=3-(-4) equation:


Simplifying
-3(x + 6) = 3 + -1(-4)

Reorder the terms:
-3(6 + x) = 3 + -1(-4)
(6 * -3 + x * -3) = 3 + -1(-4)
(-18 + -3x) = 3 + -1(-4)

Multiply -1 * -4
-18 + -3x = 3 + 4

Combine like terms: 3 + 4 = 7
-18 + -3x = 7

Solving
-18 + -3x = 7

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '18' to each side of the equation.
-18 + 18 + -3x = 7 + 18

Combine like terms: -18 + 18 = 0
0 + -3x = 7 + 18
-3x = 7 + 18

Combine like terms: 7 + 18 = 25
-3x = 25

Divide each side by '-3'.
x = -8.333333333

Simplifying
x = -8.333333333

See similar equations:

| 15(x+27)=5x+17 | | 3(b-8)=4+7(b) | | 16w+15=7 | | 18-2k=24 | | 2.3n-11=4+n | | -2(10-9x)-6x+17= | | -5(-7x+2)=165 | | 6.1c+8=7.1c-3 | | 8(r+3)-3(3r-3)=30 | | 2x+5=75 | | 2x-18+18=84+18 | | 3(4x+3)=9x | | 2=3(4n-6)+8(5n-4) | | 4t-7=10t+5 | | 4x+3-5=29 | | x^2-x+6= | | 6x+7=42-x | | -9=-(1+8x)-2(4-4x) | | 7+x=.5(4*-2) | | 12x-4=5x-32 | | 3x+5+2x=54 | | 7x+20= | | 2x^2-17x+15=0 | | 5y+3=9y-1 | | 7+x=.5(4*2) | | 5x-1=3x+13 | | 5-4k=-(4k+1) | | 6x-12+3x+26=180 | | z^2(x+1)-3z(x+1)-70(x+1)=0 | | (1.1+k)5-7.6=1.6 | | d-4=-13 | | -2(w-7)+lOw=34 |

Equations solver categories